Science teachers' views on student competences in education for sustainable development - Stouthart, Tuba; Bayram, Dury; Veen, Jan (Journal of research in science teaching, 2025)
In this study, Q methodology was used to identify 16 secondary school physics, chemistry, and biology teachers' views on competences in education for sustainable development (ESD). Our data collection instrument was grounded in the GreenComp competence framework developed by the European Commission. We captured three different viewpoints through by‐person factor analysis. The largest group, with nine science teachers, prioritized promoting evidence‐based instruction while avoiding the political, ethical, or value‐laden dilemmas inherent in sustainability issues. While they advocated addressing critical thinking and system thinking, their reasons for avoiding the dilemmas varied. Some teachers feared that addressing such dilemmas might lead to preaching their own values to students, while others felt unprepared or believed that science should remain objective and value‐free. The second largest group, with four science teachers, emphasize promoting nature and its well‐being above all other competences. Unlike the dominant group, this group of science teachers held themselves responsible for encouraging students to care for nature and to change their attitudes to behave more sustainably. The third group of teachers stood out by advocating fostering collective action in science education. While all teachers agreed on the importance of promoting foundational scientific knowledge, they also agreed on excluding politics from science education. This stance was influenced by internal factors, such as their perception of science as empirical, their perceived role as transmitters of scientific knowledge, and a lack of expertise. In total, 12 out of the 16 teachers who participated in our study suggested that subjects such as history are more suitable for addressing certain ESD competences. Additionally, external factors, such as the role of parents and assessments, were cited as potential reasons to dismiss certain ESD competences in science education.